Evaluation of different mouthwashes through their effect on their influence on the force loss of orthodontic elastic ligatures - Al-Koofee, Mohammed Kadhim; Al-Saeedi, Ruaa Riyadh Abdulnabi; Moktar, Norehan; Zainuddin, Siti LA (Journal of Medical Genetics and Clinical Biology, 2024)
Background: In several orthodontic treatments, elastomeric chains are utilised to produce force, however, this force degrades over time, which may impact tooth mobility. This study aims to investigate how different mouthwashes (Chlorhexidine 0.2%, Sensodyne, and Listerine) may affect the force degradation of two different types of elastic ligatures (Ortho Matrix and 3M Unitek) through the amount of force remaining. Materials and methods: Two control groups and six experimental groups each included 600 pieces of the elastomeric chains Ortho matrix (OM) and 3M Unitek (3M). Pieces were stretched to a 25mm thickness, placed on pins set into an acrylic block, and kept at 37°C in artificial saliva. For the duration of the study, each of the test groups spent one minute immersed in one of three distinct kinds of mouthwash. Ten continuous thermocyclers with temperatures ranging from 5 to 55 degrees Celsius were performed each day, alternating between cold and hot water baths. While calculating the forces, we considered six different time intervals: the beginning, 24 hours, 1, 2, 4, and 6 weeks. The one-way analysis of variance (ANOVA) test and the t-test were used to compare the mean force of a number of different mouthwashes, elastomeric chains, and times. A value of 0.05 was chosen as the cutoff for statistical significance. Results: Over time, both types of elastomeric chains significantly lost force at 6 weeks (p<0.05). At all times, the 3M Unitek (3M) created more force than the Ortho matrix (OM) elastomeric chain. Compared to other mouthwashes, chlorhexidine mouthwash had a substantially less impact on force degradation, with discernible very simple change when compared to control groups (Artificial saliva). Conclusion: According to findings, the 3M Unitek offered a higher force level than the other sort of elastomeric chains, and there is a difference that is clinically significant between the two types of elastomeric chains. It is possible that the pH of the mouthwashes, as opposed to other substances, contributes to the gradual loss of power over time. Mouthwashes containing chlorhexidine had the third-smallest influence on the force degradation of elastomeric chains, after Sensodyne and Listerine..